The estimate of convergence rate of the density of maximum of multivariate random variables - Jokimaitis, Arvydas (Lietuvos matematikos rinkinys, 1997)
In this paper the asymptotic of the density of the maximum of the independent identically distributed multivariate random variables is investigated. The nonuniform estimate of the convergence rate is obtained.